A Catalyst Free One‐Pot Synthesis of Coumarin Functionalized Bis‐oxazines in Ethanol at Room Temperature. Issue 37 (25th October 2019) - Bartwal, Gaurav; Khurana, Jitender M.
Abstract: Coumarin scaffolds exhibit diversified biological responses such as anticancer, anti‐Alzheimer, anticogulants, antituberculosis, antioxidants, anti‐inflammatory etc. 1, 3‐Oxazines also possess wide range of pharmacological activities. Therefore, incorporation of these two privileged scaffolds in a single entity using efficient green methodologies would be of great importance.Herein, we report a facile, efficient and catalyst free synthesis of coumarin functionalized bis‐oxazines via one‐pot condensation of 5, 7‐dihydroxy‐4‐methyl‐2 H ‐chromen‐2‐one, substituted aromatic amines and formaldehyde in ethanol at room temperature. This domino reaction provides rapid access to pharmacologically relevant molecular hybrids in short reaction time. This protocol offers advantages of mild reaction conditions, operational simplicity, avoidance of column chromatography, inexpensive starting reactants and ease of product separation. Abstract : We report facile and catalyst free synthesis of coumarin functionalized bis‐oxazines via one‐pot condensation of 5, 7‐dihydroxy‐4‐methyl‐2 H ‐chromen‐2‐one, substituted aromatic amines and formaldehyde in ethanol at room temperature. All the reactions proceeded smoothly without employing any purification technique thus making it a sustainable methodology. This environmentally benign protocol holds advantage of operational simplicity, easy workup and high yields.